Project Based Learning as a Means of Entrepreneurship Values Education in Elementary School Children - Putri, Dya Ayu Agustiana (Universitas Sebelas Maret, 2021)
Education is a process that produces qualified future generations who are ready to compete in facing the challenges of the times. The Central Statistics Agency (2020) explains that the total unemployment rate as of February 2020 is 6.88 million people, which shows that the Indonesian population still has a low interest in creating jobs. Entrepreneurial values need to be applied from an early age in order to train children's creativity in the entrepreneurial field. Based on this, the author aims to present ideas about entrepreneurial values education in elementary school age children through Project Based Learning. The method used is literature study by analyzing various related theories. The results obtained, Project Based Learning can change the mindset and prepare the next generation that is strong and mature. Elementary school children can have a vision and mission, as well as a clear and strong character as the values of entrepreneurship. Children constructively build deepening of learning with a project-based approach to real and relevant problems, and are associated with entrepreneurial values which include independent, creative, risk-taking, action-oriented, leadership, and hard working.